Using Edmodo Learning Social Network on Teaching Some Vietnamese Modules in English for Students of Primary Education Major of Tan Trao University - Chuyen, Nguyen Thi Hong (International Journal of Membrane Science and Technology, 2023)
The article is based on the practice of using Edmodo learning social networks in the world and in Vietnam to apply social networks to teach some Vietnamese modules in English for students of Primary Education major of Tan Trao University to adapt to the new normal. The application has created online classes parallel to face-to-face classes; Study guide; Evaluate; Archiving learning materials. Initial results show that: The roles of lecturers and students have changed positively; Learning activities are organized and implemented in a variety of ways; Exploiting effective learning data sources; How to evaluate effectiveness. Therefore, the use of learning social networks in teaching is an effective way to help the teaching process adapt to the new normal.